Healthy, Intelligent and Resilient Buildings and Urban Environments 2018
DOI: 10.14305/ibpc.2018.ie-4.04
|View full text |Cite
|
Sign up to set email alerts
|

Numerical investigation of a diffuse ventilation ceiling system for buildings with natural and hybrid ventilation

Abstract: The need to meet requirements, both in terms of ventilation and thermal comfort in modern buildings, has led to the development of different concepts for ventilation, among which the so-called Diffuse Ceiling Ventilation (DCV). This system makes use of the space between the ceiling slabs and the suspended ceiling as a plenum for fresh air, while the suspended ceiling itself becomes an air diffuser element. If compared to traditional solutions, this allows a higher amount of ventilation air to be injected in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 9 publications
0
1
0
Order By: Relevance
“…The results indicated that the influence of different configurations on the internal air circulation was negligible. A more comprehensive study of the "room slice" domain was carried out in [15]. Here, the isothermal hypothesis was removed to investigate the effects on the thermal comfort in the case of naturally induced airflow due to the thermal gradient between indoor and outdoor air.…”
Section: Panel Perforation Size (Mm) Perforation Rate (%)mentioning
confidence: 99%
“…The results indicated that the influence of different configurations on the internal air circulation was negligible. A more comprehensive study of the "room slice" domain was carried out in [15]. Here, the isothermal hypothesis was removed to investigate the effects on the thermal comfort in the case of naturally induced airflow due to the thermal gradient between indoor and outdoor air.…”
Section: Panel Perforation Size (Mm) Perforation Rate (%)mentioning
confidence: 99%